Traumas dentários em crianças e adolescentes periciadas no instituto médico legal de feira de Santana-Bahia - da Silva, Mona Lisa Cordeiro Asselta; Musse, Jamilly de Oliveira; De Almeida, André Henrique Do Vale; Marques, Jeidson Antônio Morais [UNESP]; Costa, Maria Conceição Oliveira (My University, 2017)
Objective: Describe the epidemiological profile of children and adolescents who had physical violence as the etiological factor of dental trauma. Methods: Case study in children and adolescents victims of violence under consideration of personal injury inquired by forensic dental experts in the IML in Feira de Santana, Bahia, using secondary data, in 01 period January 2010-31 December 2015. Results: 79 cases of physical abuse in children and adolescents were appreciated with 77.9% of them belonging to the adolescent age group (12-18 years), 85.9% classified as brunette skin and 31.2% had dental injuries. 70.1% of aggressions reached the soft tissue, followed by the tooth (24.7%), the most prevalent clinical manifestations were ecchymosis (22.1%), and dental trauma (17.6). Mouth (38.9%) and teeth (19.0%) were the most affected regions in the body at the time of the assault, and the arm (49.5%) and foot (7.4%) the most prevalent aggression tools. Conclusion: Most physical violence victims that suffered dental trauma were teenager with brunette skin. Victims who had two lesions were the ones that suffered the greatest number of dental trauma and in most cases caused by hands with punches and blows.
Dental trauma in children and teens inquired at legal medical institute in feira de Santana-Bahia
Keywords: Adolescent health; Child health; Violence